N-terminal prob-type natriuretic peptide is a marker of vascular remodelling and subclinical atherosclerosis in asymptomatic hypertensives. (29th August 2020) - Pastormerlo, Luigi E; Maffei, Stefano; Latta, Daniele Della; Chubuchny, Vladislav; Susini, Carla; Berti, Sergio; Clerico, Aldo; Prontera, Concetta; Passino, Claudio; Januzzi, James L; Emdin, Michele; Chiappino, Dante
Abstract: Background: Arterial hypertension is a main determinant of arterial remodelling and atherosclerosis. Coronary artery calcium score and carotid intima-media thickness are recognized indices of vascular remodelling. Established biohumoral markers for the diagnosis of atherosclerosis are still lacking in asymptomatic subjects with hypertension. Objectives: We aimed to test the association of plasma N-terminal pro B-type natriuretic peptide concentrations with either coronary artery calcium score or carotid intima-media thickness in asymptomatic hypertensive subjects. Methods: We conducted a case–control study on 436 hypertensi.ve and 436 age/sex-matched normotensive subjects from the population of the Montignoso HEart and Lung Project, a community-based study of asymptomatic general population ≥45 years. Subjects underwent N-terminal pro B-type natriuretic peptide measurement, echocardiography and evaluation of coronary artery calcium score and carotid intima-media thickness. Results: Hypertensive subjects had higher median coronary artery calcium score (60 (interquartile range, 30–112) vs. 15 (interquartile range 3–70) Agatson units, p  = 0.007), carotid intima-media thickness (8.6 (interquartile range 7.5–9.1) vs. 7.9 (7.1–8.4) µm, p  < 0.001) and indexed left ventricular mass (101 (interquartile range 82–126) vs. 87 (63–91) mg/m2, p  = 0.03) than controls, with no differences in left ventricular ejection fraction, diameters, E/E′, left atrial area. N-terminal pro B-type natriuretic peptide concentrations were higher in hypertensive subjects with either coronary artery calcium score ( p  = 0.008) or carotid intima-media thickness >75th ( p  < 0.006) percentile and highest in combined coronary artery calcium score/carotid intima-media thickness >75th percentile ( p  = 0.021) . In multivariable analysis, N-terminal pro B-type natriuretic peptide independently predicted either coronary artery calcium score or carotid intima-media thickness >75th percentile, but only in hypertensive subjects (odds ratio = 1.87, 95% confidence interval 1.30–2.74, p  = 0.001 and odds ratio = 1.99, 95% confidence interval 1.43–2.76, p  = 0.001). Conclusions: In asymptomatic subjects with hypertension, N-terminal pro B-type natriuretic peptide is a marker of hypertension-mediated preclinical vascular disease.